Management System of Education: Conceptual Similarity (Integration) between Japanese Learning System and Islamic Learning System in Indonesia - Munifah, Munifah; Tsani, Iskandar; Yasin, Muhamad; Tortop, Hasan Said; Palupi, Endah Kinarya; Umam, Rofiqul (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2019)
The changing times that followed the development of technology made the education system management must be updated to suit the needs and conditions of the environment. In this article, we look for information about the education system in two different countries, namely Japan and Indonesia. The purpose of this research is to find out the integration between the two countries that have different education management systems. The research method used is a descriptive qualitative method. In this research also, the research method is based on the philosophy of postpositivism, using natural conditions or objects. The instrument used to find out information on the education system in each school uses 10 questions and looks for curriculum information data in general in each country. The findings in this study found that, although the management of the education systems of the two countries was slightly different, Indonesian students could compete to continue their tertiary education to developed countries. Besides, the education system in Japan does not make students from Indonesia experience difficulties.